OTONOMI PENGELOLAAN PERGURUAN TINGGI PADA TUGAS-TUGAS POKOK PENGELOLA DAN WAKTU KERJA (Studi Kasus di STKIP PGRI Sumenep) - Asmoni Asmoni (Reflektika, 2015)
The research focus of the study 1. What are the main tasks in the scope of work managers STKIP PGRI Sumenep, 2. use of working time by the manager in STKIP PGRI Sumenep. Research shows that exposure Based on the data that has been submitted adapuan principal tasks manager in STKIP PGRI Sumenep used to analyze the workload. The basic job description at the level of the leadership, the leadership, academic executive, executive administration, academic support and administrative penunnjang have differences. The difference lies in the authority and responsibility in the organizational structure. Responsible leadership, elements of leadership helps leaders, implementers academic perform academic functions, perform administrative executive and administrative functions at the support element. The use of working time management in STKIP PGRI Sumenep. Weekday used to work is 5 days with daily allocation of work for 8 hours